Justice ; Misunderstood malady ; The Storyteller [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
A case of Justice Gutierrez on graft and corruption. A report on epilepsy, a recurrent seizure often mistaken a psychiatric illness. A mobile library set up by NEDA Director General Cielito Habito and his wife to the poor children in Laguna.
Justice (17 min.) -- Misunderstood malady (16 min.) -- The Storyteller (13 min.)
VHS.
Keywords: Judicial corruption -- Philippines; Epilepsy -- Philippines; Human services -- Philippines -- Laguna; Judges -- Philippines; Justice, Administration of -- Philippines